Implementation of Islamic values in ISMUBA curriculum to form a Rabbani generation at Muhammadiyah Sidareja High School - Haliifah Ibtisamah Abu Bakar (Universitas Ahmad Dahlan, 2022)
Indonesia's young generation is currently experiencing moral degradation due to various factors. Muhammadiyah as a large Islamic organization in Indonesia has the responsibility to educate students in Muhammadiyah schools to become a Rabbani generation in accordance with Islamic values. The purpose of this study is to analyze how the implementation of the ISMUBA curriculum at SMA Muhammadiyah Sidareja as an initial reference to form students as a Rabbani generation. This type of research is This research is descriptive qualitative research in the form of field research, collecting primary data through interviews from the principal, the head of the curriculum, the Muhammadiyas subject teacher. the results of this research show ISMUBA as a curriculum in Muhammadiyah schools is one of the breakthroughs to be able to overcome the problem of moral degradation. However, in running ISMUBA, a synergistic relationship between parents and teachers is needed, so that the goal of forming a Rabbani generation with Qur’anic spirit can be achieved.